Platelet Sensitivity to Aggregation in Normal and Diseased Groups - Sano, T; Boxer, M. G. J; Boxer, L. A; Yokoyama, M (Thrombosis and Haemostasis, 1971)
A method to estimate the sensitivity of platelets to aggregation by ADP has been described. Platelet-rich plasma was obtained from 8% trisodium citrate anticoagulated blood. ADP in trishydroxymethylaminomethane buffered saline was prepared by serial two-fold dilutions in concentrations of 2−1 through 2−18 mg/ml. Fifty μl each of platelet-rich plasma and ADP solution were mixed in a plastic test tube and agitated for 1 min. Aggregation was observed utilizing a light microscope. All procedures were performed at room temperature. The coefficient of variation in one sample was 1.4% or less and the daily variation was slight in healthy male volunteers. An advantage of this method is that it requires only a small amount of blood for the performance of many tests.In 105 healthy Japanese males, the sensitivity of platelets to ADP-induced aggregation was positively correlated with age with a correlation coefficient of 0.824.In the acute stage of thromboembolism of myocardial infarction or stroke, value of platelet sensitivity to ADP-induced aggregation was significantly higher at the 0.05 to 0.01 confidence limits than in age-, and sex-matched controls.